2018
DOI: 10.1002/jia2.25147
|View full text |Cite
|
Sign up to set email alerts
|

Prevention paradox: Medical students are less inclined to prescribe HIV pre‐exposure prophylaxis for patients in highest need

Abstract: IntroductionDespite healthcare providers’ growing awareness of pre‐exposure prophylaxis (PrEP), prescription rates remain low. PrEP is an efficacious HIV prevention strategy recommended for use with condoms but still protective in their absence. Concern about the impact of PrEP on condom use and other risk behaviour is, nonetheless, among the barriers to prescription commonly reported. To understand the implications of this concern for PrEP access, we examined how medical students’ willingness to prescribe PrE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 36 publications
1
39
2
Order By: Relevance
“…In a survey of health directors in North Carolina ( N = 56), a perceived lack of suitable PrEP candidates was reported by 26% of respondents from departments not prescribing or referring individuals for PrEP [ 23 ]. Recently, a paradox concerning perception of risk and willingness to prescribe has been noted in an online survey completed by 111 medical students [ 49 ]. Results showed that willingness to prescribe was inconsistent with patient risk, with fewer students willing to prescribe PrEP if the patient was engaging in riskier behaviors such as not using condoms or having multiple partners.…”
Section: Low Perception Of Hiv Risk As a Barrier To Prep Uptakementioning
confidence: 99%
“…In a survey of health directors in North Carolina ( N = 56), a perceived lack of suitable PrEP candidates was reported by 26% of respondents from departments not prescribing or referring individuals for PrEP [ 23 ]. Recently, a paradox concerning perception of risk and willingness to prescribe has been noted in an online survey completed by 111 medical students [ 49 ]. Results showed that willingness to prescribe was inconsistent with patient risk, with fewer students willing to prescribe PrEP if the patient was engaging in riskier behaviors such as not using condoms or having multiple partners.…”
Section: Low Perception Of Hiv Risk As a Barrier To Prep Uptakementioning
confidence: 99%
“…Additionally, graduate medical courses should work to debunk racial and other stereotypes about risk compensation, as such biases impede provider willingness to prescribe PrEP (23)(24)(25)34). Future work could examine the extent to which hands-on experiences with high-risk populations (e.g., via clinical rotations) impact both willingness to prescribe and refer.…”
Section: Interdisciplinary Approaches To Prep Carementioning
confidence: 99%
“…To date, there is limited data about healthcare professional students' knowledge and perceptions of PrEP as future potential prescribers. The few studies were limited to medical students (23)(24)(25)(26) and did not include other health professional students who may play an active role in PrEP care, such as those in nurse practitioner, or pharmacy training programs. Calabrese and colleagues surveyed medical students regarding the influence of patient race (23), sexual orientation (24), and sexual behavior (25) on clinical decision-making related to PrEP.…”
Section: Introductionmentioning
confidence: 99%
“…Even though many individuals do not change their condom use behavior after starting PrEP, there is evidence that the concerns of some clinicians about behavioral change may lead them not to offer PrEP to MSM, particularly black MSM, 11 or reserve PrEP for heterosexual serodifferent couples attempting to conceive. 11,12 It is likely that some individuals with knowledge of the high efficacy of PrEP in preventing HIV infection will change their behavior and that higher-risk behavior is contributing to the current STI epidemic. 10 However, concerns about behavioral change after starting PrEP should not decrease the willingness of clinicians to offer PrEP.…”
mentioning
confidence: 99%